Nurses job satisfaction identified by personal preferences and perceived saturation divergence: a comparative cross-sectional study in Czech hospitals between 2011 and 2021 - Jiri Vevoda; Daniela Navratilova; Ondrej Machaczka; Petr Ambroz; Sarka Vevodova; Marco Tomietto (BMC, 2023)
Abstract Background The perception of the quality of care provided by the medical institution to patients is directly affected by the job satisfaction of nurses. The feeling of job satisfaction is caused besides other things by the subjective expectations of employees about what their work should provide them with in return. The aim of the study is to evaluate and compare job satisfaction of hospital nurses in the Czech Republic in 2011 and 2021 by identifying differences between their personal preferences and perceived saturation. Methods The respondents are hospital nurses in the Czech Republic in 2011 and 2021. A developed questionnaire was used to determine the job satisfaction factors. The order of factors of personal preferences, perceived saturation and differences between them was compiled. For evaluation was used the Euclidean distance model that enables to capture the order and determine the significance given by the distance in which the factors are located. Results At the top of personal preferences of hospital nurses, the factors salary and patient care are in the first two places with a similar distance. The salary factor is the most preferred by hospital nurses in both evaluated periods, and at the same time there is the greatest discrepancy between personal preferences and perceived saturation. By contrast, image of profession and working conditions were sufficiently saturated by the employer in both periods, but nurses do not significantly prefer these factors. Conclusions The salary and patient care (i.e. the mission of the nurse's work itself) are at the top of personal preferences of hospital nurses, with an exclusive position among other factors. We consider it important that the hospital management emphasizes them in the management of hospital nurses. At the same time, the patient care is perceived by the hospital nurses as one of the most saturated factors - in contrast to salary, which is located at the complete opposite pole as the least saturated factor and therefore emerges from the mutual comparison as the factor with the greatest degree of divergence. The stated conclusions are valid for both compared periods. New method of data evaluation was successfully tested.